Effectiveness of the PRI Model (Psycho-Religious Intervention) in Improving the Psychological Well-Being of Cancer Patients: A Randomized Controlled Trial - Priyanto Priyanto; Weni Hastuti (Talenta Publisher, 2026)
Cancer imposes a heavy psychological burden that significantly reduces patients’ quality of life; however, conventional psychosocial interventions often overlook the need for spiritual coping, which is of vital importance to patients in religious cultures. This study aims to examine the effectiveness of the Psycho-Religious Intervention (PRI) Model, which combines psychological education with spiritual practices such as contemplative prayer, on the psychological well-being (PWB). This study employed a single-blind, parallel-group, pre-posttest Randomized Controlled Trial (RCT) design, involving 60 homogeneous cancer patients recruited into the intervention (n=30) and control (n=30) groups. The intervention group received the PRI Model delivered over four days (two sessions per day), while the control group received standard care. The data were analyzed using independent t-test and paired t-test. The results of the study show that the PRI Model significantly improved the total PWB score (p=0.010). The intervention group recorded an average increase of 15.54 points, whilst the control group rose by only 3.74 points, representing a 14.03% increase in the total PWB score compared with the control group. The PRI model demonstrated superiority across five of the six PWB dimensions, with the greatest impact observed in the Autonomy dimension (19.41%, p=0.001), accompanied by significant improvements in the Positive Relationships, Self-Acceptance, Environmental Mastery and Life Purpose dimensions. This study provides strong evidence that the PRI Model is an effective, culturally sensitive intervention for enhancing the psychological well-being of cancer patients. Consequently, the PRI Model is recommended for validation as a standard approach in psycho-oncology care. Keyword: Cancer, Psychological Well-Being, Psycho-Religious Intervention, Randomized Control Trial